Case study of the transcritical CO2 system in the National Speed Skating Oval - Guan, J.; Qiao, Y.; Cui, C.; Wang, B.; Yin, X.; Cao, F.; Wang, X. (Applied Thermal Engineering, 2025)
Due to the influence of economic and policy factors, the requirements for the reliability and energy-saving of large-scale industrial CO2 refrigeration systems are much higher than those of small and medium-sized systems. This study collected and analyzed the data of the transcritical/subcritical CO2 ice-making system of NSSO. Different from the research on large-scale ice-making systems that mostly rely on theoretical models and focus on performance simulation, this study conducts multidimensional analyses based on actual operation data. First, system operation characteristics and steady-state performance were evaluated, along with heat recovery performance and energy consumption. Additionally, ice surface temperature data were collected to assess ice quality. Finally, a comprehensive exergy loss analysis was conducted to identify major sources of irreversible losses, providing insights for energy-saving optimizations in large-scale refrigeration systems. Results indicate that the system exhibits stable startup behavior, achieving operational stability within 8 to 10 min. Heat recovery contributes to approximately 40 % electricity savings compared to PTC heating. Moreover, ice surface temperature fluctuations are effectively controlled, with a maximum coefficient of variation of only 5.01 %. Exergy analysis shows that the heat exchanger at high-pressure side, compressor, and ejector account for more than 80 % of the total exergy loss. The transcritical CO2 refrigeration system demonstrates substantial energy-saving and environmental benefits, making it a promising solution for artificial ice-making applications.